Implementation of Pancasila as a National Identity in Era 4.0 - Anugrah Ratri Pangestuti; Salma Septyaningrum; Yunita Nur Hidayah; Riska Andi Fitriono (CV. Rayyan Dwi Bharata, 2022)
Values, histories, and ideals are a community bond called national identity. National Identity itself has factors that affect the dynamics of globalization. Globalization can develop various aspects of life such as science, technology, values and culture. In this study using the literature study method by collecting various references and secondary sources such as journals, books, articles, research reports, and various good internet sites. Efforts to maintain national identity in the era of globalization can be studied in literature studies that can be studied in literature studies that can strengthen the problem.The challenges in facing the era of the industrial revolution 4.0 are: (1) based on pancasila (2) increasing human resources based on the value of pancasila (3) choosing pancasila as the state ideology.